AU-rich element-mediated mRNA decay can occur independently of the miRNA machinery in mouse embryonic fibroblasts and drosophila S2-cells - Helfer, Stephanie; Schott, Johanna; Stoecklin, Georg (PLOS ONE, 2012)
AU-rich elements (AREs) are regulatory sequences located in the 3′ untranslated region of many short-lived mRNAs. AREs are recognized by ARE-binding proteins and cause rapid mRNA degradation. Recent reports claimed that the function of AREs may be - at least in part - relayed through the miRNA pathway. We have revisited this hypothesis using dicer knock-out mouse embryonic fibroblasts and cultured Drosophila cells. In contrast to the published results, we find no evidence for a general requirement of the miRNA pathway in the function of AREs. Endogenous ier3 mRNA, which is known to contain a functional ARE, was degraded rapidly at indistinguishable rates in wild type and dicer knock-out mouse embryonic fibroblasts. In cultured Drosophila cells, both ARE-containing GFP reporter mRNAs and the endogenous cecA1 mRNA were resistant to depletion of the mi/siRNA factors dcr-1, dcr-2, ago1 and ago2. Furthermore, the Drosophila miRNA originally proposed to recognize AU-rich elements, miR-289, is not detectably expressed in flies or cultured S2 cells. Even our attempts to overexpress this miRNA from its genomic hairpin sequence failed. Thus, this sequence cannot serve as link between the miRNA and the AU-rich element mediated silencing pathways. Taken together, our studies in mammalian and Drosophila cells strongly argue that AREs can function independently of miRNAs.
Gesehen am 04.09.2018